2016
DOI: 10.2147/ndt.s108834
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes of whole brain in patients with comitant strabismus: evidence from a diffusion tensor imaging study

Abstract: ObjectiveThe aim of this study was to investigate the fractional anisotropy (FA) and mean diffusivity (MD) using a diffusion tensor imaging technique and whole-brain voxel-based analysis in patients with comitant strabismus.Patients and methodsA total of 19 (nine males and ten females) patients with comitant strabismus and 19 age-, sex-, and education-matched healthy controls (HCs) underwent magnetic resonance imaging examination. Imaging data were analyzed using two-sample t-tests to identify group difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…In a study of anisometropic amblyopia, Liang et al (39) reported decreased amplitude of low-frequency fluctuation values in the bilateral precuneus cortex in adults with anisometropic amblyopia, and the degree of reduction was associated with disease severity, suggesting that patients with bilateral precuneus neurons exhibited weaker activity. In addition, Huang et al (40) used DTI technology to analyze changes in whole brain microstructure in patients with strabismus. They found that the FA value of bilateral precuneus was significantly increased, suggesting enhanced fiber bundle integrity in this brain area.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of anisometropic amblyopia, Liang et al (39) reported decreased amplitude of low-frequency fluctuation values in the bilateral precuneus cortex in adults with anisometropic amblyopia, and the degree of reduction was associated with disease severity, suggesting that patients with bilateral precuneus neurons exhibited weaker activity. In addition, Huang et al (40) used DTI technology to analyze changes in whole brain microstructure in patients with strabismus. They found that the FA value of bilateral precuneus was significantly increased, suggesting enhanced fiber bundle integrity in this brain area.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Hayakawa et al 58 suggested that the cerebellar posterior vermis was related to saccadic eye movements. Huang et al 61 found the mean diffusivity values in the bilateral cerebellum posterior lobe were significantly decreased in comitant strabismus patients, and Tan et al 54 found DC values of comitant exotropia strabismus patients reduced in the right cerebellum posterior lobe. Moreover, lower ALFF value of strabismus subjects has been observed in the bilateral cerebellum posterior lobe.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Similarly, in previous voxel-wise studies, FA values were increased in the medial frontal gyrus of patients with comitant exotropia. 11 The voxel-wise degree centrality in the temporal gyrus was increased in a study of the functional brain activity network. 17 Given that the ILF is not only the major association pathway that links the occipital cortex with the temporal lobe (an indirect pathway is also linked to the frontal lobe), 18 we speculate that this phenomenon might indicate more numerous dense connections or less branching within fiber bundles, representing the underlying neuropathologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Likewise, previous investigators have also found that FA values were decreased in the IFO. 11 The IFO connects the frontal and occipital lobes along with the lateral border of the caudate nucleus. The IFO is thought to be vital for integrating information among these remote brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation